Bauxite-based castable for permanent layer of blast furnace trough and preparation method thereof
Patent Information
- Application Number
- CN202611210916.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-16
AI Technical Summary
解决了现有永久层浇注料在长期高温服役过程中易出现开裂、粉化、渣液渗透及高温稳定性不足等问题
(1)本发明以铝矾土骨料和细粉构建主体骨架,采用硅溶胶作为无水泥结合剂,并引入碳化硅细粉、活性Al2O3微粉、部分稳定氧化锆粉、纳米氧化物及低熔点玻璃粉等功能组分,通过骨架致密化与基质强化协同作用提升浇注料整体性能。铝矾土骨料采用多级颗粒级配,通过高温原位形成刚玉、莫来石等稳定相,结合合理的多级颗粒级配,使材料获得较高的体积密度与结构稳定性,有效降低显气孔率,从而有效抑制铁水、炉渣及氧化性气体的渗透通道,提升永久层浇注料在高温服役条件下的抗侵蚀与抗氧化能力。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of refractory material preparation technology, specifically relating to a bauxite-based castable for the permanent layer of a blast furnace tapping trough and its preparation method. Background Technology
[0002] The blast furnace tapping trough is a crucial channel in the blast furnace ironmaking system for receiving and transporting high-temperature molten iron and slag. Its lining typically consists of a working layer, a permanent layer, and an insulation layer. The working layer is in direct contact with the molten iron and slag, primarily serving to resist erosion, corrosion, and oxidation. The permanent layer, located outside the working layer and between the insulation layer and the working layer, mainly supports the working layer structure, reduces heat conduction outwards, and acts as a second safety barrier to prevent molten iron and slag from further penetrating into the insulation layer and the trough's steel shell, thereby ensuring the overall structural stability and safe operation of the tapping trough.
[0003] Although the permanent lining does not directly contact molten iron and slag, it continuously withstands high-temperature conduction, temperature gradient changes, and periodic thermal shock from the working layer during long-term service. When the working layer experiences localized erosion or damage, the permanent lining may also be indirectly affected by molten slag and oxidizing atmospheres. Therefore, permanent lining materials often experience problems such as sintering shrinkage, loose structure, pulverization, and cracking in practical use, leading to a decrease in their density and structural stability. This weakens their thermal insulation and support functions and may cause the steel shell temperature to rise, increasing operational safety risks.
[0004] Furthermore, under high temperature and oxygen-containing atmospheres, the lining materials of the tapping trench, especially the working layer materials, are prone to oxidation reactions, leading to the gradual loss of carbon phases or easily oxidized components, thereby reducing their structural integrity and corrosion resistance. If the permanent layer cannot effectively suppress the oxidizing atmosphere and heat transfer, it will indirectly accelerate the deterioration of the working layer and shorten the overall service life of the lining. Therefore, the permanent layer material not only needs to possess low thermal conductivity, high strength, good volume stability, and excellent thermal shock resistance, but also a certain degree of density and oxidation resistance to slow down the diffusion of oxidizing media into the lining system. This will indirectly protect the working layer during long-term service, extend its service life, and improve the overall safety of the tapping trench.
[0005] Currently, the permanent lining of blast furnace tapping troughs is mainly composed of bauxite-based castables, but these materials suffer from high porosity, low density, and poor high-temperature stability. Under long-term high-temperature service conditions, they are prone to structural degradation and performance decline, making it difficult to simultaneously meet the performance requirements of high strength, impermeability, and thermal shock resistance. Therefore, developing a permanent lining material for blast furnace tapping troughs with higher density, lower porosity, excellent oxidation resistance, and self-healing crack capabilities is of great significance for improving the service safety of tapping troughs, extending lining life, and reducing maintenance costs. Summary of the Invention
[0006] The purpose of this invention is to provide a bauxite-based castable for the permanent layer of a blast furnace taphole and its preparation method. This castable uses bauxite aggregate and fine powder to construct the main skeleton, employs silica sol as a cementless binder, and introduces functional components such as silicon carbide fine powder, active Al2O3 micro powder, partially stabilized zirconium oxide powder, nano-oxides, and low-melting-point glass powder. The overall performance of the castable is improved through the synergistic effect of skeleton densification and matrix strengthening. This invention solves the problems of cracking, pulverization, slag penetration, and insufficient high-temperature stability that existing permanent layer castables easily encounter during long-term high-temperature service.
[0007] The present invention is specifically achieved through the following technical solution: According to the present invention, a bauxite-based castable for the permanent layer of the blast furnace tapping trough includes, by mass percentage, 65-75% bauxite aggregate, 10-20% bauxite fine powder, 2-8% silicon carbide fine powder, 5-10% active Al2O3 micro powder, 1-4% partially stabilized zirconium oxide powder, 0.5-2% nano oxides, and 0.5-3% glass powder.
[0008] The aforementioned blast furnace tapping trough permanent layer uses bauxite-based castable material with silica sol as a binder, and the silica sol content accounts for 4-6% of the total raw material mass.
[0009] The aforementioned blast furnace tapping trough permanent layer uses bauxite-based castable refractory, with the added water accounting for 4-6% of the total raw material mass.
[0010] The aforementioned bauxite-based castable for the permanent layer of the blast furnace tapping trough preferably uses Grade II bauxite as the bauxite aggregate, which is a mixture of bauxite with different particle sizes. The different particle sizes of bauxite include bauxite with particle sizes of 8-5 mm, 5-3 mm, 3-1 mm, and less than 1 mm. Preferably, the mass percentage of bauxite with a particle size of 8-5 mm is 30-40%, the mass percentage of bauxite with a particle size of 5-3 mm is 25-35%, the mass percentage of bauxite with a particle size of 3-1 mm is 15-25%, and the mass percentage of bauxite with a particle size of less than 1 mm is 10-20%.
[0011] The aforementioned blast furnace tapping trough permanent layer of bauxite-based castable material has the following particle size distribution: bauxite fine powder ≤74 μm, silicon carbide fine powder ≤200 μm, active Al2O3 micro powder ≤10 μm, and partially stabilized zirconium oxide powder ≤74 μm.
[0012] The aforementioned blast furnace tapping trough permanent layer of bauxite-based castable refractory, wherein the nano-oxide is one or both of nano-alumina and nano-titanium oxide, and the nano-alumina particle size is ≤50 nm and the nano-titanium oxide particle size is ≤50 nm.
[0013] The aforementioned blast furnace tapping trough permanent layer of bauxite-based castable refractory has the following chemical composition of glass powder: 50-60% SiO2, 20-30% B2O3, 10-15% Na2O, 2-5% Al2O3, and 2-5% CaO.
[0014] Furthermore, the alumina-based castable for the permanent layer of the blast furnace tapping trough is prepared according to the following method: S1. Weigh the raw materials according to the mass percentage. The raw materials include 65-75% bauxite aggregate, 10-20% bauxite fine powder, 2-8% silicon carbide fine powder, 5-10% active Al2O3 micro powder, 1-4% partially stabilized zirconium oxide powder, 0.5-2% nano oxides, and 0.5-3% glass powder. Add all the raw materials to the mixer and dry mix for 4-20 minutes to obtain a uniform dry mix. S2. Take silica sol and water and mix them evenly beforehand to obtain a silica sol binding solution; S3. Slowly add the silica sol binder obtained in step S2 to the uniform dry mix obtained in step S1, stirring continuously during the addition process. Wet mix for 4~20 min to obtain a castable slurry with construction fluidity. Cast the castable slurry into shape, cure at room temperature for 24 h after shaping, and then dry at 110℃ for 24 h to obtain the bauxite-based castable for the permanent layer of the blast furnace tapping trough.
[0015] Preferably, in step S2, the amount of silica sol used is 4-6% of the total mass of the raw materials, and the amount of water used is 0.5-2% of the total mass of the raw materials.
[0016] Preferably, the silica sol solid content is 35-40 wt%.
[0017] The bauxite-based castable for the permanent layer of the blast furnace tapping trough, prepared according to the aforementioned method, has an apparent porosity of 12-14%, preferably 12.6-13.8%, and a bulk density of 2.8-3.0 g / cm³. 3 The preferred value is 2.89-2.93 g / cm³. 3 The room temperature flexural strength is 13-16 MPa, preferably 13.6-15.5 MPa; the room temperature compressive strength is 83-95 MPa, preferably 83.5-92.6 MPa; after three water-cooled thermal shock cycles at 1100℃, the flexural strength retention rate is 72-79%, preferably 72.2-78.3%, and the oxide layer thickness is 2-3.1 mm.
[0018] Compared with the prior art, the present invention has at least the following advantages: (1) This invention uses bauxite aggregate and fine powder to construct the main skeleton, adopts silica sol as a cementless binder, and introduces functional components such as silicon carbide fine powder, active Al2O3 micro powder, partially stabilized zirconia powder, nano oxides and low melting point glass powder. The overall performance of the castable is improved through the synergistic effect of skeleton densification and matrix strengthening. The bauxite aggregate adopts multi-level particle size distribution, and stable phases such as corundum and mullite are formed in situ at high temperature. Combined with reasonable multi-level particle size distribution, the material obtains high bulk density and structural stability, effectively reduces apparent porosity, and thus effectively inhibits the penetration channels of molten iron, slag and oxidizing gases, and improves the corrosion resistance and oxidation resistance of permanent layer castable under high temperature service conditions.
[0019] (2) The present invention uses silica sol as a cement-free binder, which avoids the formation of low-melting-point phases caused by the introduction of CaO in traditional cement systems, and can improve the erosion resistance and high-temperature stability of the material.
[0020] (3) The present invention introduces nano-oxides, which can promote the sintering densification process by filling micropores, making the matrix structure more continuous and dense, reducing the diffusion rate of oxygen and slag media, and improving the material's impermeability and oxidation resistance.
[0021] (4) The present invention adds some stabilized zirconia powder, which utilizes its phase transformation toughening effect to effectively inhibit the propagation of thermal stress-induced cracks, thereby improving the thermal shock resistance of the material.
[0022] (5) The present invention introduces low melting point glass powder, which can form a viscous glass phase at microcracks and pores under high temperature conditions, thereby achieving self-sealing of cracks and repair of pores, further blocking the penetration channels of molten iron, slag and oxidizing gas, thereby improving the service stability of the material. Detailed Implementation
[0023] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0024] Unless otherwise specified, all conditions in the following embodiments were performed under conventional conditions or conditions recommended by the manufacturer. Raw materials and reagents whose manufacturers are not specified are all commercially available products. Unless otherwise specified, the scientific and technical terminology and experimental methods of this invention are based on the conventional understanding and existing standard methods of those skilled in the art. It should be understood that the parameters such as temperature and holding time involved in this invention are approximate values and are used for illustrative purposes; those skilled in the art can make reasonable adjustments according to actual needs.
[0025] All percentages in the following examples are by mass. The particle size of bauxite fine powder is ≤74 μm, silicon carbide fine powder is ≤200 μm, active Al₂O₃ micro powder is ≤10 μm, partially stabilized zirconia powder is ≤74 μm, nano-alumina particle size is ≤50 nm, and nano-titanium oxide particle size is ≤50 nm. The chemical composition of the glass powder includes: 50-60% SiO₂, 20-30% B₂O₃, 10-15% Na₂O, 2-5% Al₂O₃, and 2-5% CaO. The partially stabilized zirconia powder used in the examples was purchased commercially.
[0026] Example 1 A type of bauxite-based castable for permanent layer of blast furnace tapping trough, comprising the following raw materials by mass percentage: 70% grade II bauxite aggregate, 15% fine bauxite powder, 4% fine silicon carbide powder, 6% active Al2O3 micro powder, 2% partially stabilized zirconia powder, 1% nano Al2O3 powder, and 2% glass powder.
[0027] The binder is used at 5% of the total mass of the dry material (i.e., raw material), and the water is added at 1% of the total mass of the dry material (i.e., raw material). The binder is a silica sol with a solid content of 35-40%.
[0028] The Grade II bauxite aggregate is a mixture of bauxite with different particle sizes, including bauxite with particle sizes of 8-5 mm, 5-3 mm, 3-1 mm, and less than 1 mm. Among them, bauxite with a particle size of 8-5 mm accounts for 35% of the Grade II bauxite aggregate by mass, bauxite with a particle size of 5-3 mm accounts for 28% of the Grade II bauxite aggregate by mass, bauxite with a particle size of 3-1 mm accounts for 20% of the Grade II bauxite aggregate by mass, and bauxite with a particle size of less than 1 mm accounts for 17% of the Grade II bauxite aggregate by mass.
[0029] The permanent layer of the blast furnace tapping trough is prepared using bauxite-based castable refractory according to the following method. S1. Weigh out different particle sizes of Grade II bauxite aggregate, bauxite fine powder, silicon carbide fine powder, active Al2O3 micro powder, partially stabilized zirconium oxide powder, nano Al2O3 powder and glass powder according to the above raw material ratio, add them to the mixer and dry mix for 4 minutes to obtain a uniform dry mixture. S2. Take silica sol and water according to the mass percentage, and mix the silica sol and water evenly in advance to obtain a silica sol binding solution; S3. Slowly add the silica sol binder obtained in step S2 to the uniform dry mix obtained in step S1, stirring continuously during the addition process, and wet mix for 4 minutes to obtain a castable slurry with construction fluidity; pour the castable slurry into the mold for casting and molding, and perform vibration degassing treatment. After molding, cure at room temperature for 24 hours, and then dry at 110℃ for 24 hours to obtain the bauxite-based castable for the permanent layer of the blast furnace tapping trough.
[0030] The bauxite-based castable obtained in this embodiment was heat-treated at 1400℃ for 3 hours under carbon embedding conditions. Its bulk density, apparent porosity, room temperature flexural strength, room temperature compressive strength, thermal shock resistance, and oxidation resistance were tested according to national standards GB / T 2997-2015, GB / T 3001-2017, GB / T 5072-2023, GB / T 30873-2014, and GB / T13244-1991. The results are as follows: apparent porosity 13.2%, bulk density 2.90 g / cm³. 3 The room temperature flexural strength is 14.8 MPa, the room temperature compressive strength is 88.2 MPa, and after three water-cooled thermal shocks at 1100℃, the flexural strength retention rate is 75.1%, and the oxide layer thickness is 3.1 mm.
[0031] Example 2 A type of bauxite-based castable for permanent layer of blast furnace tapping trough, comprising the following raw materials by mass percentage: 68% Grade II bauxite aggregate, 14% fine bauxite powder, 5% fine silicon carbide powder, 7% activated Al2O3 micro powder, 3% partially stabilized zirconium oxide powder, 1% nano TiO2 powder, and 2% glass powder.
[0032] The binder is used at 4% of the total mass of the dry material (i.e., raw material), and the water added is 0.5% of the total mass of the dry material (i.e., raw material). The binder is a silica sol with a solid content of 35-40%.
[0033] The Grade II bauxite aggregate is a mixture of bauxite with different particle sizes, including bauxite with particle sizes of 8-5 mm, 5-3 mm, 3-1 mm, and less than 1 mm. Specifically, bauxite with a particle size of 8-5 mm accounts for 38% of the Grade II bauxite aggregate by mass, bauxite with a particle size of 5-3 mm accounts for 30% of the Grade II bauxite aggregate by mass, bauxite with a particle size of 3-1 mm accounts for 18% of the Grade II bauxite aggregate by mass, and bauxite with a particle size of less than 1 mm accounts for 14% of the Grade II bauxite aggregate by mass.
[0034] The preparation method and specific parameters of the bauxite-based castable for the permanent layer of the blast furnace tapping trough are the same as in Example 1.
[0035] The bauxite-based castable obtained in this embodiment was heat-treated at 1400℃ for 3 hours under carbon embedding conditions. Its bulk density, apparent porosity, room temperature flexural strength, room temperature compressive strength, thermal shock resistance, and oxidation resistance were tested according to national standards GB / T 2997-2015, GB / T 3001-2017, GB / T 5072-2023, GB / T 30873-2014, and GB / T13244-1991. The results are as follows: apparent porosity 12.6%, bulk density 2.93 g / cm³. 3 The room temperature flexural strength is 15.5 MPa, the room temperature compressive strength is 92.6 MPa, and after three water-cooled thermal shocks at 1100℃, the flexural strength retention rate is 78.3%, and the oxide layer thickness is 2.8 mm.
[0036] Example 3 A type of bauxite-based castable for permanent layer of blast furnace tapping trough, comprising the following raw materials by mass percentage: 72% grade II bauxite aggregate, 12% fine bauxite powder, 6% fine silicon carbide powder, 5% active Al2O3 micro powder, 2% partially stabilized zirconia powder, 0.5% nano Al2O3 powder, 0.5% nano TiO2 powder, and 2% glass powder.
[0037] The binder is used at 6% of the total mass of the dry material (i.e., raw material), and the water added is 1.5% of the total mass of the dry material (i.e., raw material). The binder is a silica sol with a solid content of 35-40%.
[0038] The Grade II bauxite aggregate is a mixture of bauxite with different particle sizes, including bauxite with particle sizes of 8-5 mm, 5-3 mm, 3-1 mm, and less than 1 mm. Among them, bauxite with a particle size of 8-5 mm accounts for 34% of the Grade II bauxite aggregate by mass, bauxite with a particle size of 5-3 mm accounts for 30% of the Grade II bauxite aggregate by mass, bauxite with a particle size of 3-1 mm accounts for 22% of the Grade II bauxite aggregate by mass, and bauxite with a particle size of less than 1 mm accounts for 14% of the Grade II bauxite aggregate by mass.
[0039] The preparation method and specific parameters of the bauxite-based castable for the permanent layer of the blast furnace tapping trough are the same as in Example 1.
[0040] The bauxite-based castable obtained in this embodiment was heat-treated at 1400℃ for 3 hours under carbon embedding conditions. Its bulk density, apparent porosity, room temperature flexural strength, room temperature compressive strength, thermal shock resistance, and oxidation resistance were tested according to national standards GB / T 2997-2015, GB / T 3001-2017, GB / T 5072-2023, GB / T 30873-2014, and GB / T13244-1991. The results are as follows: apparent porosity 13.8%, bulk density 2.89 g / cm³. 3The room temperature flexural strength is 13.6 MPa, the room temperature compressive strength is 83.5 MPa, and after three water-cooled thermal shocks at 1100℃, the flexural strength retention rate is 72.2%, and the oxide layer thickness is 2.6 mm.
[0041] It should be noted that the above embodiments 1-3 were carried out in the laboratory. When used to make a permanent layer in the tapping trough of a blast furnace on site, vibration exhaust treatment can be omitted in step S3.
[0042] Comparative Example This comparative example describes a common bauxite-based castable for the permanent layer of a blast furnace taphole. The raw materials, by mass percentage, include: 70% Grade II bauxite aggregate, 10% fine bauxite powder, 8% fine SiC powder, 7% activated Al2O3 micropowder, and 5% aluminate cement. The added water is 5% of the total dry material (i.e., raw materials). During preparation, each raw material is taken according to its mass percentage and added to a mixer for dry mixing for 5 minutes to obtain a uniform dry mix. Water is then added according to the added water amount and wet-mixed for 5 minutes to obtain a castable slurry. The castable slurry is poured into a mold for casting and molding, followed by vibration and degassing. After molding, it is cured at room temperature for 24 hours and then dried at 110℃ for 24 hours to obtain a common cement-bonded bauxite-based castable.
[0043] The properties of the ordinary cement-bonded bauxite-based castable were tested using the same test method as in Example 1. The results are as follows: apparent porosity 17.8%, bulk density 2.75 g / cm³. 3 The flexural strength at room temperature is 9.5 MPa, the compressive strength at room temperature is 62.3 MPa, and after three water-cooled thermal shock cycles at 1100℃, the flexural strength retention rate is 58.1%, and the oxide layer thickness is 4.7 mm. The overall performance of this ordinary cement-bonded bauxite-based castable is not as good as that of the bauxite-based castables obtained in Examples 1-3 of this invention.
[0044] Compared to the comparative examples, Examples 1-3 of this invention use silica sol as a cement-free binder, which avoids the introduction of CaO into the cement system and reduces the formation of low-melting-point phases at high temperatures, thereby improving the high-temperature stability and corrosion resistance of the material. Simultaneously, this invention introduces some stabilized zirconia powder, nano-oxides, and low-melting-point glass powder into the raw materials, which, through phase transformation toughening, promoting sintering densification, and crack self-sealing, respectively, improve the material's thermal shock resistance, oxidation resistance, and impermeability. Therefore, the bauxite-based castable prepared by this invention is more suitable for the long-term high-temperature service environment of the permanent layer in the blast furnace tapping trough, effectively supporting the working layer, improving impermeability, and protecting the steel shell of the trough.
[0045] The above description is merely an embodiment of the present invention and is not intended to limit the present invention in any way. The present invention can also have other embodiments based on the above structure and function, which will not be listed hereafter. Therefore, any simple modifications, equivalent changes, and alterations made by those skilled in the art to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A bauxite-based castable for the permanent layer of a blast furnace tapping trough, characterized in that, By weight percentage, the raw materials include 65-75% bauxite aggregate, 10-20% bauxite fine powder, 2-8% silicon carbide fine powder, 5-10% active Al2O3 micro powder, 1-4% partially stabilized zirconium oxide powder, 0.5-2% nano oxides, and 0.5-3% glass powder.
2. The bauxite-based castable for the permanent layer of the blast furnace tapping trough as described in claim 1, characterized in that, The bauxite aggregate is Grade II bauxite, and it is a mixture of bauxite with different particle sizes, including bauxite with particle sizes of 8-5 mm, 5-3 mm, 3-1 mm, and less than 1 mm. Among them, bauxite with a particle size of 8-5 mm accounts for 30-40% of the bauxite aggregate by mass, bauxite with a particle size of 5-3 mm accounts for 25-35% of the bauxite aggregate by mass, bauxite with a particle size of 3-1 mm accounts for 15-25% of the bauxite aggregate by mass, and bauxite with a particle size of less than 1 mm accounts for 10-20% of the bauxite aggregate by mass.
3. The bauxite-based castable for the permanent layer of the blast furnace tapping trough as described in claim 1, characterized in that, The particle size of bauxite fine powder is ≤74 μm, the particle size of silicon carbide fine powder is ≤200 μm, the particle size of active Al2O3 micro powder is ≤10 μm, and the particle size of partially stabilized zirconium oxide powder is ≤74 μm.
4. The bauxite-based castable for the permanent layer of the blast furnace tapping trough as described in claim 1, characterized in that, The nano-oxide is one or both of nano-alumina and nano-titanium oxide, with nano-alumina particle size ≤50 nm and nano-titanium oxide particle size ≤50 nm.
5. The bauxite-based castable for the permanent layer of the blast furnace tapping trough as described in claim 1, characterized in that, The chemical composition of the glass powder includes: 50-60% SiO2, 20-30% B2O3, 10-15% Na2O, 2-5% Al2O3, and 2-5% CaO.
6. The bauxite-based castable for the permanent layer of the blast furnace tapping trough as described in claim 1, characterized in that, Prepared according to the following method: S1. Weigh the raw materials according to the mass percentage. The raw materials include 65-75% bauxite aggregate, 10-20% bauxite fine powder, 2-8% silicon carbide fine powder, 5-10% active Al2O3 micro powder, 1-4% partially stabilized zirconium oxide powder, 0.5-2% nano oxides, and 0.5-3% glass powder. Add all the raw materials to the mixer and dry mix for 4-20 minutes to obtain a uniform dry mix. S2. Take silica sol and water and mix them evenly beforehand to obtain a silica sol binding solution; S3. Slowly add the silica sol binder obtained in step S2 to the uniform dry mix obtained in step S1, stirring continuously during the addition process. Wet mix for 4~20 min to obtain a castable slurry with construction fluidity. Cast the castable slurry into shape, cure at room temperature for 24 h after shaping, and then dry at 110℃ for 24 h to obtain the bauxite-based castable for the permanent layer of the blast furnace tapping trough.
7. The bauxite-based castable for the permanent layer of the blast furnace tapping trough as described in claim 1, characterized in that, In step S2, the amount of silica sol used is 4-6% of the total mass of the raw materials, and the amount of water used is 0.5-2% of the total mass of the raw materials.
8. The bauxite-based castable for the permanent layer of the blast furnace tapping trough as described in claim 6 or 8, characterized in that, The silica sol has a solid content of 35-40 wt%.
9. The bauxite-based castable for the permanent layer of the blast furnace tapping trough as described in any one of claims 6-8, characterized in that, Its apparent porosity is 12-14%, and its bulk density is 2.8-3.0 g / cm³. 3 The flexural strength at room temperature is 13-16 MPa, the compressive strength at room temperature is 83-95 MPa, and the flexural strength retention rate is 72-79% after three water-cooled thermal shocks at 1100℃.